Association of Killer Cell Immunoglobulin-Like Receptor Genes with Pandemic Influenza A (H1N1)pdm09 Infection in Critically Ill Macedonian Patients - Petlichkovski, Aleksandar; Milenkovikj, Zvonko; Eli Djulejic; Bisera Jefremovska; Haris Babacic; Ljubomir Ivanovski; Kondova Topuzovska, Irena (Scientific Foundation SPIROSKI, 2012)
Background: Infection by the pandemic influenza A (H1N1)pdm09 virus results in significant pathology disease in many cases in different populations worldwide. The natural killer (NK) cells are among the major effectors important in early innate immune responses to viral infections, interacting with host cells through their activating or inhibiting receptors. Aim: The aim of this study was to analyze Killer Ig-Like Receptor (KIR) gene polymorphisms in critically ill Macedonian patients with pandemic influenza A (H1N1)pdm09 infection. Material and Methods: The studied sample consists of 63 critically ill Macedonian patients with pandemic influenza A (H1N1)pdm09 infection. The population genetics analysis package, Arlequin, was used for analysis of the data. Results: We found that all 16 KIR genes were observed in the studied individuals and framework genes (KIR3DL3, KIR3DP1, KIR2DL4, and KIR3DL2) were present in all individuals. The results of tested linkage disequilibrium (LD) among KIR genes demonstrated that KIR genes present a wide range of linkage disequilibrium. Comparison of KIR gene frequencies between critically ill H1N1/09 Macedonian patients and healthy subjects reveals statistically significant difference for frequency of KIR2DL1 (F=1 in the patients group, and 0.94 in the control group, p=0.045). Conclusion: We did not found any significant association of all 16 KIR genes or KIR genotypes with critically ill (H1N1)pdm09 Macedonian patients, except for the KIR2DL1.
Keywords: Killer immunoglobulin-like receptor (KIR); KIR genotyping; PCRSSP; patients with (H1N1)pdm09 infection; gene polymorphism